LARGE-SCALE CARTOGRAPHIC REPRESENTATION OF RELIEF FEATURES FROM SANDYZATION PROCESS - Costa, Bibiana Salvador Cabral da; Sluter, Claudia Robbi; Iescheck, Andrea Lopes; Rodrigues, Éder Luís da Silva (Boletim de Ciências Geodésicas, 2021)
In topographic maps, contour lines and elevation points usually represent the variation of height and slope. Contour lines interval defines the level of detail for relief representation. Geomorphological features we can identify on maps are related to contour lines generalization. In this study, we aim to define the necessary level of detail for the cartographic representation of relief features from the sandyzation process. The methodology comprises: defining the relief features associated with sandyzation at the study area by literature review; describing the aspects of data survey using Remotely Piloted Aircraft (RPA) to generate the orthophoto mosaic and the Digital Surface Model (DSM); and using the DSM to extract contour lines at different scales. We defined eight relief features (denudational landform, rill, ravine, micro-residual hill, dune, depositional fan, concentrated flow, and gully) for contour cartographic representation at 1:5,000, 1:1,000, 1:500, 1:200, and 1:100 scales. The results show the scales in which the relief features have their geomorphological characteristics better represented by contours lines. Since there is no reference for suitable scales for the cartographic representation of landforms related to the sandyzation process, this study can contribute to geomorphological researches in areas where this process occurs.